Transgenerational effects of parental bisphenol S exposure on zebrafish (Danio rerio) reproduction. (July 2022) - Hao, Liping; Ru, Shaoguo; Qin, Jingyu; Wang, Weiwei; Zhang, Jie; Wei, Shuhui; Wang, Jun; Zhang, Xiaona
Abstract: Bisphenol S (BPS) is extensively used for production of polycarbonates and other commodities, and is often detected in environment and biota. Parental BPS exposure has been reported to interfere with reproductive development of offspring, but limited information is available on its multigenerational reproductive toxicity. In our present study, zebrafish ( Danio rerio ) were exposed to BPS (1 and 100 μg/L) from 3 hpf to 120 dpf, and the effects on reproduction, sex steroid hormones, DNA methylation levels and gene transcription involved in steroidogenesis and DNA methylation were investigated in unexposed F1-2 offspring. The results showed that 100 μg/L BPS exposure increased DNA methylation in F1 testes, and 1 μg/L BPS led to DNA methylation in F2 ovaries. The increased DNA methylation levels led to decreased expression of steroidogenic enzymes, including cyp11a, cyp17 and 3βhsd, which might be a main reason for the elevated plasma 17 β- estradiol and decreased testosterone levels. In addition, sex ratio indicated a female dominance trend, and reproductive capacity of male fish was severely impaired. Overall, these findings suggest that parental BPS exposure impairs reproductive development of unexposed offspring via DNA methylation and BPS-induced epigenetic modification inheritance has a long-term effect on the fitness and sustainability of fish populations. Graphical abstract: Image 1 Highlights: Parental bisphenol S exposure disturbed gonadal DNA methylation of unexposed offspring. Parental bisphenol S exposure skewed the sex ratio toward females in F1 and F2 offspring. Estrogenic effects of bisphenol S were transmitted across generations via DNA methylation.